Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus. Issue 21 (2nd November 2021) - Sun, Hui-Hui; Lv, Wen-Yan; Tan, Jie; Tang, Yu-Cheng; Zhu, Hui; Qu, Jian-Bo; Li, Jing; Wu, Jian-Ping; Chang, Xi-Wen; Yang, Zhi-Chun; Wang, Wen-Xuan; Chen, Zu-Hui; et al.
Abstract: Three previously undescribed dammarane triterpenoid glycosides (1-3 ) along with five known analogues (4-8 ) were isolated from the leaves of Cyclocarya paliurus . Their structures and configurations were determined on the basis of comprehensive spectroscopic analyses, chemical hydrolysis and DFT GIAO 13 C NMR calculation. All the isolates were evaluated cytotoxic activities against seven human cancer cell lines (MCF-7, PC-3, Du145, NCI-H1975, PC-9, SKVO3 and HepG2). Moreover, compound 4 showed a wide spectrum of cytotoxicity against human cancer cells with IC50 values ranging from 11.31 to 29.51 µM. Graphical Abstract: